2015
DOI: 10.14319/ijcto.34.11
|View full text |Cite
|
Sign up to set email alerts
|

Statistical methods to evaluate the correlation between measured and calculated dose using quality assurance method in IMRT

Abstract: The objective of this study is to validate a procedure based on a statistical method to assess the agreement and the correlation between measured and calculated dose in the process of quality assurance (QA) for intensity-modulated radiation therapy (IMRT). Methods: Fifty-six fields for head and neck cancer treatment from 10 patients were analyzed. For each patient a treatment plan was generated using Eclipse TPS ®. To compare the calculated dose with the measured dose a CT-scan of solid water slabs (30 × 30 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…In Figure 4, percentage dose difference of most of H&N plans were negative which suggest under dosage, same results reported by Chung et al [22]. Figure 5 demonstrates that there is a lack of correlation between DD and γ passing rates, same results reported in literature [20], with R 2 of 0.0509.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In Figure 4, percentage dose difference of most of H&N plans were negative which suggest under dosage, same results reported by Chung et al [22]. Figure 5 demonstrates that there is a lack of correlation between DD and γ passing rates, same results reported in literature [20], with R 2 of 0.0509.…”
Section: Discussionsupporting
confidence: 81%
“…Hence confidence limit for DD depends on the proper assessment of dose calculation. [20]. Previous studies suggest that positioning error of multileaf collimator, inadequate dosimetric data of MLC in treatment planning system, complexity of tumor site, mode of delivery, and mishandling of dosimeter by user may cause discrepancy in measurement of dose difference [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23- 24 The gamma tool shows a visual representation of the difference in dose distribution to the patient. They reported that the only realistic dose distribution is that evaluated by the clinical results obtained to the benefit of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a challenge in radiation therapy for cancer treatment is to deliver the physical dose as close as possible to the prescription dose, depending on the accuracy of the dose calculation algorithms. The planed dose, given by the TPS, for each field could be compared with measured dose using Quality Assurance (QA) protocols according to the international recommendations (1)(2)(3)(4). The gamma index (γ) tool allows to compare the spatial dose distribution displaying the dose difference with γ-maps (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%